2022
DOI: 10.1177/09596518221123365
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of axially moving web in multi-span roll-to-roll microcontact printing system

Abstract: This article presents theoretical dynamic analysis of a vibrating axially moving web of a multi-span / multi-roll microcontact printing system and experimental measurements of the system’s frequency response. A unique lab-scale microcontact printing machine with high-speed web handling capabilities is used. The axially moving web is modeled as a string and as a membrane. Then, numerical results of both models are compared with experimentally obtained response. The experiment is run for both case of constant ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…17 Since high-magnitude oscillation can cause structural failure, numerous studies have looked into a range of techniques to control the excessive amplitude of oscillation of moving beam like structures, such as the passive/active control strategies, feedback control scheme, and boundary control technique to smoothen the beam movement. [18][19][20][21] The vibration problem in other complex engineering structures has been studied in previous studies. [22][23][24][25][26] Thermal contraction/expansion is developed in the presence of a temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Since high-magnitude oscillation can cause structural failure, numerous studies have looked into a range of techniques to control the excessive amplitude of oscillation of moving beam like structures, such as the passive/active control strategies, feedback control scheme, and boundary control technique to smoothen the beam movement. [18][19][20][21] The vibration problem in other complex engineering structures has been studied in previous studies. [22][23][24][25][26] Thermal contraction/expansion is developed in the presence of a temperature gradient.…”
Section: Introductionmentioning
confidence: 99%
“…Using the finite difference method (FDM), dynamic response in terms of vibration amplitude and frequencies for moving string was presented in Ali and Hawwa 17 . Since high‐magnitude oscillation can cause structural failure, numerous studies have looked into a range of techniques to control the excessive amplitude of oscillation of moving beam like structures, such as the passive/active control strategies, feedback control scheme, and boundary control technique to smoothen the beam movement 18–21 . The vibration problem in other complex engineering structures has been studied in previous studies 22–26 …”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the modes of vibration, it was concluded that the effect of fluid on the lower modes was more significant than the higher modes of vibration. The dynamics of axially moving materials in printing applications had also been studied extensively [22][23][24]. Nonhomogeneous boundary conditions were used in the investigation of the dynamic characteristics of a moving beam by Zhang et al [25].…”
Section: Introductionmentioning
confidence: 99%